An evaluation of orthodox and emerging alternative approaches to the industrial policy in the context of economic development - Lamola, Leonard Sekhohliwe (My University, 2013)
In a broad sense, an industrial policy is aimed at influencing the structure of an economy. Justin Lin (2010), argues that the best way to upgrade a country’s endowment structure is to develop its industries according to the comparative advantages determined by its given endowment structure at that time. Then he assumes that the economy would be most competitive, the economic surplus predominant, and the capital accumulation and the upgrading of factor endowment structure will be the fastest possible. He further proposes that the private enterprises should enter industries according to the country’s comparative advantages, relative factor prices must fully reflect the relative abundance of those factors as prices can only be determined through competition in a ―well-functioning‖ market. Therefore, the market should be the basic institution of the economy. The proposed essay will conduct a critical analysis of structuralism and industrial policy as propagated within the ―New Structural Economics‖ realm as proposed by Justin Lin, a former World Bank chief economist. The proposed inquiry would attempt to underline that the Newly Industrialised Countries showed that specific institutions have performed a critical role in guiding market forces towards industrial development. Notably is the state as an institution in its developmental role in guiding economic strategy and industrial policies. Therefore, the basic argument is that despite the eminence of the orthodox economic approach and its responses to the recent economic crises there are numerous contradictions, including weaknesses as advocated by Lin’s approach to developmental issues and the role of industrial policy, expressly with regard to the developing world.
Keywords: Industrial policy; Economic development; Developing countries